Multiple Cause of Death, 1990 ([Verlag nicht ermittelbar], 1994)
This data collection presents information about the causes of all deaths occurring in the United States during 1990. Data are provided concerning underlying causes of death, multiple conditions that caused the death, place of death and residence of the deceased (e.g., region, division, state, county), whether an autopsy was performed, and the month and day of the week of the death. In addition, data are supplied on the sex, race, age, marital status, education, usual occupation, and origin or descent of the deceased. The multiple cause of death fields were coded from the MANUAL OF THE INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES, INJURIES, AND CAUSE-OF-DEATH, NINTH REVISION (ICD-9), VOLUMES 1 AND 2.